Aspectos comportamentais e clínicos da cárie dentária na primeira infãncia: Leticia Vargas Freire Martins Lemos - Lemos, Letícia Vargas Freire Martins [UNESP] (2013)
The aim of this research was to analyze the behavioral and the clinical aspects of dental caries in children from 0 to 48 months, who attended a dental care preventive government program in the State of São Paulo, Brazil, named ‘Dentistry for babies’. The research was divided in three studies. The first study was a prospective observational cohort study, with two hundred children participants in the program, who were assigned into two groups: G1 - children that joined the program during the first year of life (n=126); and G2 - children that joined the program between 13 and 18 months (n=74). In this study, the children were examined every three months until they were 48 month old. Dental caries incidence/children’s age was statistically correlated to assiduity, cariogenic diet, day/night oral hygienic and night breastfeeding variables. The data were analyzed using the Chi-Square and Fisher’s tests. Survival univariate (Kaplan-Meier) and multivariate (Cox) analysis were carried out, with 5% significant level. The second and third studies evaluated 465 children including the 200 who participated in the cohort study. The children were assigned into three groups: G0 – babies whose mothers joined the program when still pregnant (n=50); G1 – babies that joined the program during the first year of life (n=230); and G2 – children that joined the program between 13 and 18 months (n=185). The data was collected through tactile and visual clinical examination by a calibrated investigator (k>0.8). The parents also answered a questionnaire including questions about the children’s diet habits, day and night hygienic habits, night feeding habits, parents’ education level, social economical condition, and children’s behavior during home and professional treatment... (Complete abstract click electronic access below)